2020
DOI: 10.1097/ccm.0000000000004624
|View full text |Cite
|
Sign up to set email alerts
|

Practices in Triage and Transfer of Critically Ill Patients: A Qualitative Systematic Review of Selection Criteria

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 143 publications
1
12
0
1
Order By: Relevance
“…1 Many publications have developed and evaluated triage selection criteria, but there remains a significant knowledge gap and the final criteria are subject to socio-ethical debate. [2][3][4] Preferably, triage is averted, but when necessary, the decision should be guided by evidence-based medical criteria. Since March 2020, many studies have been published regarding the clinical characteristics of patients suffering from a SARS-CoV-2 infection in both smaller (n=58, 5 n=200 6 ) and larger cohorts (n>5000 [7][8][9] ).…”
Section: Open Accessmentioning
confidence: 99%
“…1 Many publications have developed and evaluated triage selection criteria, but there remains a significant knowledge gap and the final criteria are subject to socio-ethical debate. [2][3][4] Preferably, triage is averted, but when necessary, the decision should be guided by evidence-based medical criteria. Since March 2020, many studies have been published regarding the clinical characteristics of patients suffering from a SARS-CoV-2 infection in both smaller (n=58, 5 n=200 6 ) and larger cohorts (n>5000 [7][8][9] ).…”
Section: Open Accessmentioning
confidence: 99%
“… 7 The lack of specific criteria for ICU admission decisions has been recently pointed out. 8 Whereas a decision supporting framework was developed to address the issue of limiting or not life-sustaining treatments in the ICU, 9 no such framework exists for triage. Yet, deciding whether to admit a patient to the ICU is often complex, and physicians mostly rely on their clinical judgement.…”
Section: Introductionmentioning
confidence: 99%
“…The population understands some words, like "therapeutic obstinacy, " and in fact the idea is to use these words, but not everyone is really able to understand them." (Participant 4, age range [31][32][33][34][35][36][37][38][39][40] One participant added that the difficulty to address endof-life issues is also common among HCPs and not only family members: "Colleagues lack sensitivity on this. .…”
Section: Paternalism's Comebackmentioning
confidence: 99%
“…Think about how difficult this is to accept." (Participant 4, age range [31][32][33][34][35][36][37][38][39][40] Participants also reported that the absence of the family members, who could not be close to the patients in the hospital and frequently interact with the care team, accentuated this form of paternalism and prevented a shared decision making approach.…”
Section: Paternalism's Comebackmentioning
confidence: 99%